The Effectiveness of Reciprocal Peer Tutoring (RPT) On the Academic Performance of Students in Mathematics - Henson, Luzale Dioso; Hagos, Luisito C.; Villapando, Rosanna A. (INTI University College, 2009)
The importance of facilitating study and practice materials that are consistent with graded assessments and instructional objectives is well known, if not commonly used, in educational practice. This study focused on the effectiveness of Reciprocal Peer Tutoring (RPT) against the traditional approach in learning. A well-established procedure of RPT was developed for an effective peer tutoring process that can be implemented with a minimum of teacher participation was used in this study. Students engaging in RPT are paired at random and given instruction on how to prepare practice exercises and or multiple choice format tests within the scope of the topic as Indicated in study guides provided to them. During an RPT activity, each student of a dyad is independently responsible for synthesizing course content, preparing math exercises and constructing multiple-choice format test questions, complete with answers and explanation. Each dyad then administers practice test to each other every RPT session and prior to formal class examinations. Group monitors are also appointed to give feedback on RPT activities and also served as on-Line peer tutor via e-mail. This one-on-one email-based mentoring will enable students under RPT group and the researcher to thrive in the online learning environment. Access to lesson outlines and sample problems through @yahoogroups.com was established. Likewise, posting of assignments aligned to e-tutor lesson modules can be accessed through the same e-tutor bulletin board. This study aimed to determine the effectiveness of RPT on the academic performance of engineering students in College Algebra was conducted at New Era University, College of Engineering and Technology during the second semester of Academic Year 2008-2009 with a sample size of 35 first year engineering students for each sample group using cluster sampling method. It was found that RPT Intervention was more effective in causing significant increase in student’s performance and RPT was a more effective strategy than that of the traditional chalk and board to improve student’s performance In College Algebra. Based on the findings and conclusions, the researcher recommended considering the use of RPT as an alternative instructional Intervention to improve student’s performance In College Algebra and in other courses. Furthermore, it was recommended to modify/strengthen the research to determine whether RPT procedures can be redesigned to make them more meaningful for the learning needs of college students.